“Rendimiento, población de medoidogyne sp, contenido y caracterización de aceite en 10 accesiones promisorias de sacha inchi (plukenetia volubilis L.) en la E.E.A. “el porvenir” Juan Guerra-San Martín” - Benito García, María Teresa (2009)
We evaluated 1 O accessions of. volubilis Plukenetia L. "Sacha lnchi" from the Collection Division of the National Research on Genetic Resources and Biotechnology - SODIRGEB the Experimental Station ';El Porvenir" - INIA, with the aim of identifying promising accessions with higher grain yield, dry Populations Meloidogyne spp low, oil content and characterization. The study was developed in the experimental fields of the EEA "El Porvenir", Lot A1 (W 76 ° 5 ', south latitude 6 ° 35'; 232 m.s.n.m.m.), the land is clayey nature, flat, with pH 6, 76, MO: 2.34% P: 25.77, K: 280.20, according to the analysis of fertility. Far ten years, rice was grown under irrigation, and three years later, cotton, and is currently in the process of fallow far two years until the beginning of our assessments. The variables studied were: Germination (º1) 1 st Appearance 2nd and 3rd pair of true leaves (d.d.s.), emission guidelines (d.d.s), Home of flower buds (d.d.s.); Home flowering male and female (d.d.s.), Home Harvest (d.d.s.), number of pods per plant, yield of fresh and dried capsules (kg I ha), diameter of capsules per accession (mm), diameter of seed (mm), shell weight (g), seed index (g), total seed weight (9)% of Shell, % seed, dry seed yield (kg I ha),% Moisture, % Oil, Characterization of oil (lodine value, peroxide index and saponification), Population of Meloidogyne spp in roots and soil and weather data. The statistical analysis used a completely randomized block design (DBCA) ten treatments with three replications was used and 5 experimental units (plants), Statistical analysis consisted of an analysis of variance (ANVA) 5% error far variables under study. To discriminate the best accessions, we used the mean separation test using the test of discrimination Duncan multiple ranges at 95% reliability. The tests were conducted under the Sub-project financed by INCAGRO "Generation of elite lines of Sacha lnchi (Plukenetia volubilis L.), high productivity, high in omega oils and tolerant to nematodes (Meloidogyne spp), for cultivation in the Amazon region, in partnership with the lnstitute for Agrarian lnnovation INIA and the lnstitute of Tropical Crops - ICT. According to the information processing field and laboratory results indicate that the T7 - PER000409 - Putumayo and T2 - PER000395 - Pinto Recodo, are superior in dry seed yield per hectare, with 160.34 and 111.21 kg, respectively, the T1 O - PER000420 - Putumayo and T9 - PER000416 - Chazuta are shown with a smaller number of juveniles of Meloidogyne spp I 20 g of root with 996 and 1514 respectively, and finally the T3 - PER000396 - San Roque de Cumbaza and T5 - PER000405 - Capelo, have a higher oil content with 53.3167 and 52. 7867%, respectively, for the characterization of the oil was determinad that the T3 - PER000396 - San Roque and Cumbaza of T1 - PER000394 - Band Shilcayo show higher rates of iodine with 192.38 and 187.60, g del/ 100 g de aceite respectively, with respect to the peroxide T9 - PER000416 - Chazuta and T8 - PER000415 - Brazil, have lower Peroxide with 5.29 milieq /1000 g de aceite for both cases and respect to the saponification T1 - PER000394 - Band Shilcayo and T9 - PER000416 - Chazuta bring 17 4.28 and 144.63 mg KOH /g de aceite respectively. The information may increase understanding of the accessions conservad in the Collection IN1A - SUDIRGEB Agricultura! Experimental Station of the "El Porvenir", this will be a tool for planning future management of germplasm collections and, in future research on genetic improvement of the species.